Nutrient Digestibility of Beef Cattle Ration with Total Mixed Fiber Amoniation (TMFA) as Basal Feed and Organic Mineral Supplementation by In Vitro - Afnur Imsya; Yuanita Windusari; Riswandi Riswandi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The research was aimed to obtain the level of organic minerals supplementation with Total mixed fiber Amoniation (TMFA) as basal feeding for the improvement of nutrient digestibility in rumen. Technique of research conducted by In Vitro technique. The method used in this research is a Completely Randomly Designed (CRD) with 4 treatments and 4 replications. P1: 60% amoniation TMF + 0 x Organic macro minerals (Ca, P, and S) NRC (2000) + 15% Swamp Legumes. P2: 60% ammonia TMF + 0.75 x Organic macro minerals (Ca, P, and S) NRC (2000) + 15% Swamp Legum, P3: 60% ammonia TMF + 1 x Organic macro minerals (Ca, P, and S) NRC (2000) + 15% Legum Swamp P4: 60% amoniation TMF + 1.5 x Organic macro minerals (Ca, P, and S) NRC (2000) + 15% Swamp Legum. Each treatment was added with an organic micro-mineral consisting of 40 ppm organic Zn, 10 ppm organic Cu, 0.10 ppm organic Se, and 0.30 ppm organic Cr. The parameters measured in the in-vitro technique were, measurement of nutrient digestibility which consists of dry matter and organic matter, crude protein, crude fiber, NDF and ADF. The results showed that organic mineral supplementation had significantly different effect (P <0.05) on nutrient digestibility (dry matter, organic matter, crude protein, crude fiber, ADF, NDF). The conclusion of this study was that organic mineral supplementation of Ca, P and S 1.5 times of requirement according to NRC (2000) gave the best results for in vitro nutrient beef digestion with Total mixed fiber ammoniation (TMFA) as basal feed and supplementation of l5% legume swamp (Kemon air).Keywords: Amoniation, total mixed fiber, organic mineral, nutrient digestibility